Front Cover: Binding of Hydrophobic Guests in a Coordination Cage Cavity is Driven by Liberation of "High‐Energy" Water (Chem. Eur. J. 7/2018). Issue 7 (30th November 2017) - Metherell, Alexander J.; Cullen, William; Williams, Nicholas H.; Ward, Michael D.
Abstract : The cavity of a cubic coordination cage in water contains an ordered array of water molecules in a 'high‐energy' arrangement, because of the shortage of hydrogen‐bonding interactions arising from contact with the hydrophobic cage surface. Binding of hydrophobic guests releases these water molecules into the bulk solution, where they can optimise their hydrogen‐bonding interactions with the solvent; the resulting enthalpy gain is a major contributor to guest binding. More information can be found in the Full Paper by M. D. Ward et al. onpage 1554 .